Organizational Support and its Relation with Organizational Justice and Organizational Compliance: Applied Study on Physicians Who Work in Some Government Hospitals in Riyadh City - Al Rashidi, Ali (The Arab Journal of Administration, 2019)
This research aimed to determine levels of organizational support, organizational justice and organizational compliance and to identify relation between organizational support and organizational justice, and its relation with organizational compliance, also the relation between organizational justice and organizational compliance, a sample of (230) physicians has been taken and they represented (40%) of the research population which is (575) physicians. The results revealed that availability rate related to different dimensions of organizational support was high, except dimension of administrative policy was average, the results also showed that there was extreme relation with statistical significance between organizational support and organizational justice and organizational compliance. The results also revealed there was significant statistical effect for difference of research samples response about all dimensions as per variable of experience years in favor of (10) years and above, versus less than (10) years. The most important recommendations indicated to importance to care of applied administrative policies to go along with expectations and objectives of employees and to be based on scientific and technical bases and participation of employees in development of policies related to progress of medical services in order to improve performance and to achieve organizational compliance. It is important to develop strategic training vision for all medical specialties, and to specify supported resources for training and to identify actual needs for these specialties.